The Analysis Of Abnormal Returns Before And During The Covid-19 Pandemic On Hotel, Restaurant And Tourism Sub-Sector Stocks Listed On Idx - Holiviana, Adinda; Bhilawa, Loggar; Harun, Harun (International Environmental Conferrence on Biosustainability Advancement, 2024)
The purpose of this study was to determine the difference in average abnormal returns before and during COVID-19 in hotel, restaurant and tourism sub-sector stocks listed on the IDX. The type of data used in this study is secondary data. Determination of the sample in this study using purposive sampling method with certain criteria so that 37 samples were obtained. The analysis technique used in this research is one-sample t-test and paired sample t-test with an observation period of 100 days. This study uses daily data on hotel, restaurant and tourism sub-sector stocks. The results of the one-sample t-test show that the abnormal return is not significant around the window period so it can be concluded that covid-19 has no effect on abnormal return. Meanwhile, the results of the paired sample t-test show a significance value of 0.876> 0.05. From these results it can be concluded that there is no significant difference in average abnormal returns before and during the COVID-19 pandemic.